Photosystem I fluorescence as a physiological indicator of hydrogen production in Chlamydomonas reinhardtii. (February 2019) - Anandraj, Akash; White, Sarah; Mutanda, Taurai
Highlights: Chlamydomonas reinhardtii produces more hydrogen in higher light intensities. The rETR of PSI exceeded that of PSII for all control and experimental cultures. Three stages of hydrogen synthesis, pre-H2 ; H2 production and post H2 production. Photosynthetic parameters recorded the upregulation of PSI during H2 production. Abstract: This study investigated the interrelations between hydrogen synthesis and Photosystem I electron transport rate in Chlamydomonas reinhardtii . The fluorescence of both photosystems (PS I and PS II) was monitored using a Dual Pulse Amplitude Modulated (PAM) Fluorometer. Hydrogen synthesis was induced by eliminating sulphur from the growth media (TAP-S). Multiple physiological parameters [rETR, Y (I), Y (II), NPQ, α, Fv /Fm and YI:YII] were recorded using the Dual PAM and correlated to hydrogen produced. There was a 66% increase in Photosystem I rETRmax during hydrogen production. A significant direct correlation existed between PS 1 rETRmax and hydrogen evolution values over the ten-day period (r = 0.895, p < 0.01) indicating that PS I can be considered as a driver of H2 production. Significant correlations between rETRmax of PS I and H2 evolution suggest a novel physiological indicator to monitor H2 production during the three critical phases identified in this study.